SOCIALIZATION OF WOOD CHARCOAL GASIFICATION USING DOWNDRAFT GASIFIER - Vidian, Fajri; Fitriani, Heni; Arief, Taufik; Alian, Helmy; Hadi, Qomarul; Amri, Julil; Aprianti, Tine; Ramadhan, Daud; Maulana, Gilang Rifki; Manurung, Samuel Takkas; Siregar, Edwin Fernando; Ramadhan, Rizky Fajar; Repaldo, Repaldo; Muslim, Muhammad; Ramadhoni, Muhammad Fathur Arya; Sarie, Tri Mulyani; Aulia, Nia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The reduction in fossil energy requires alternative energy that can be renewed. Wood charcoal is one of the alternative sources that can be renewed. Wood charcoal is used to produce energy through direct combustion until now, such as in Pulau Semambu Village, Ogan Ilir, and South Sumatra. The Gasification Method is one technique for converting wood charcoal into gas fuel. This method is not widely known by the community, especially the Pulau Semambu Village, Ogan Ilir people. This Community Service aims to socialize wood charcoal gasification to produce gas fuel in the Pulau Semambu Village Community, South Sumatra. Community service is carried out through Presentations, Q&As, discussions, and demonstrations. The demonstration results showed that the Pulau Semambu Community was very interested in the material provided and the demonstration of making gas fuel from wood charcoal with a gasification process. The demonstration shows that 3 kg of fuel can produce gas for about 50 minutes. The gas fuel formed is identified by the combustion of the resulting gas, which makes the flame.